Immunofluorescence and Biochemical Investigation of the Protective Effects of Naringin and Diosmin on the Freezability of Merino Ram Semen - Ömür, Ali Doğan; Kaynar, Özgür; İleritürk, Mustafa; Özkaraca, Mustafa; Öztürk, Ali Erdem; Bodu, Mustafa; Şahin, İpek Nur; akarsu, serkan (Springer Science and Business Media LLC, 2022)
Abstract
In this study, the effects of diosmin and naringin on freezability of ram semen were investigated. For this purpose, 6 Merino rams were used during the breeding season. The ejaculates were pooled after being collected from the rams. Pooled ejaculates were divided into 6 groups as control (C; no additive) Naringin (1, 2, and 4 mM) and Diosmin (2 and 4 mM) groups, and then reconstituted with TRIS-based diluent. Pooled semen was equilibrated, placed in 0,25 mL straws with 10 × 107 sperm cells in each straw and frozen in liquid nitrogen vapor. After waiting for 24 hours, the straws were thawed at 37 oC for 25 s and analyzes were made. There was no statistical difference in total motility between the groups. D2 and D4 preserved the integrity of the plasma membrane better than the other groups. D4 showed better effect than other groups in terms of acrosome integrity, there was no difference between the groups in terms of mitochondrial activity. In the analysis of the sperm membrane lipid profile, it was observed that the diosmin added group had the highest lipid-phospholipid ratio. In the sperm membrane protein profile analysis, it was observed that both additives had protective effects at different levels. The highest total protein amount was seen in D4 and N4 groups. 8-OhDG positivity was more common in the control group than in the diosmin and naringin groups. Cu-Zn SOD positivity was less in the control group but more intense in all other groups. The positives were especially in the acrosome parts of the sperm cells.
Keywords: Male; Cryopreservation; Sheep; Superoxide Dismutase; Cell Membrane; Spermatozoa; Antioxidants; Semen Analysis; Oxidative Stress; Cryoprotective Agents; Semen; Flavanones; Sperm Motility; Animals; Diosmin; Acrosome; Semen Preservation